A New Approach To Solve Fuzzy Non-Linear Equations Using Fixed Point Iteration Algorithm - Saha, Goutam Kumar; Shirin, Shapla (GANIT: Journal of Bangladesh Mathematical Society, 2013)
A non-linear equation over linear fuzzy real numbers is called a fuzzy non-linear equation. In Classical Mathematics a non-linear equation can be solved by using different types of numerical methods. In this paper a new approach has been introduced to get approximate solutions with the help of Fixed Point Iteration Algorithm. Graphical representation of the solutions has also been drawn so that anyone can achieve the idea of converging to the root of a fuzzy non-linear equation. DOI: http://dx.doi.org/10.3329/ganit.v32i0.13641 GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 32 (2012) 15 21